Life quality of diabetic patients - Belkis Mercedes Vicente Sánchez; Gisela Zerquera Trujillo; Dania Peraza Alejo; Eduardo Castañeda Álvarez; Jorge Luís Irizar Hernández; Tiana Bravo Valladares (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Introduction: Diabetes mellitus is a significant health problem worldwide, since it is one of the most frequent non-transmissible diseases as for the variety and intensity of complications associated with it. Objective: To assess some physical, psychic and social aspects related with life quality of these patients. Methods: A descriptive, cross-sectional study was developed in the in the Centre for Care and Education of Diabetic Patients, between 2006 and 2007. The universe was formed by 148 diabetic patients (type II) that received ambulatory assistance in that institution. Variables: age, sex, years suffering from that disease, associated diseases and nutritional assessment according to the body mass index. Results: There was grater incidence of females, most of the patients were between 40 and 59 years; it was significant the association of diabetes with hypertension, mainly in overweight patients. Life quality was poorer with more years of diseases evolution, the obese patients and those with peripheral vascular disease. Conclusion: Even when life quality of diabetic patients is not generally deteriorated, there is a negative disposition towards the disease.